INVESTIGATING THE EFFECTIVENESS OF QUESTION-GENERATION STRATEGY IN ENHANCING NARRATIVE TEXT COMPREHENSION AMONG EFL LEARNERS - Hatta Ira, Jamilah; Reflinda; Melani, Melyann; Roza, Veni (Universitas Mahaputra Muhammad Yamin, 2025)
Many students struggle with reading comprehension because they do not know how to identify key information, are less engaged in learning, and have limited exposure to interactive strategies. This study examined the effect of the question-generation strategy on ninth-grade students’ comprehension of narrative texts at MTsN 2 Agam. Employing a quasi-experimental non-equivalent control group design, the research involved 122 students across five classes, with two classes selected: IX.1 (25 students) as the experimental group and IX.2 (24 students) as the control group. The experimental group received instruction through the question-generation strategy, while the control group was taught using conventional methods. Reading comprehension was assessed using a multiple-choice test, and the data were analyzed through normality and homogeneity checks, followed by paired-sample and independent-sample t-tests. The findings revealed a significant effect of the intervention, with the experimental group achieving greater gains from pre-test to post-test compared to the control group (Sig. < 0.05). These results suggest that the question-generation strategy effectively enhances reading comprehension and encourages more active and meaningful learning in EFL classrooms.